2017
DOI: 10.1111/bjhp.12249
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of younger men's experience of heart attack (myocardial infarction)

Abstract: Themes broadly overlapped with the qualitative literature on younger adult MI. However, some themes (e.g., loss of 'maleness' post-MI, and ambivalence towards MI risk factors) appeared unique to this study. Themes were also discussed in relation to risk factors for anxiety and depression and how this might inform clinical care for a younger, male population. Statement of contribution What is already known on this subject? Myocardial infarction (MI) morbidity is not declining in England for under-45s. Adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…Studies have found that young adults with specific individual conditions have a sense of being different; struggle with a shift from an identity of healthy to sick; and feel that the challenges they face are not age-appropriate. [24][25][26][27] Relevant to the impact of LTCs on identity is the concept of biographical disruption. 28,29 For those with LTCs, there is a biographical disruption between the individual's definition of themselves with regard to the past, the present and the future.…”
Section: Young Adults With Ltcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that young adults with specific individual conditions have a sense of being different; struggle with a shift from an identity of healthy to sick; and feel that the challenges they face are not age-appropriate. [24][25][26][27] Relevant to the impact of LTCs on identity is the concept of biographical disruption. 28,29 For those with LTCs, there is a biographical disruption between the individual's definition of themselves with regard to the past, the present and the future.…”
Section: Young Adults With Ltcsmentioning
confidence: 99%
“…Other studies exclusively with young adults have also touched on this topic. Studies have found that young adults with specific individual conditions have a sense of being different; struggle with a shift from an identity of healthy to sick; and feel that the challenges they face are not age‐appropriate …”
Section: Introductionmentioning
confidence: 99%
“…In qualitative studies, a “heightened sense of mortality” was described by the participants throughout the first year after diagnosis (Lacharity, 1999 ; Andersson et al, 2013 ; Joubert et al, 2013 ), although it was described less often by men for whom it was difficult to accept death as a nearby possibility (Merritt et al, 2017 ). Emotional distress and the heightened sense of mortality were found in several expressions of fear: of dying in their sleep, of dealing with another MI (Andersson et al, 2013 ), of pain (Joubert et al, 2013 ), or of other injuries provoked by the disease (Lacharity, 1999 ; Koutrolou-Sotiropoulou et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The patients also felt guilt and responsibility with regards to their family and to past bad lifestyle choices (McAnirn et al, 2015). These feelings seemed to last up to a year later, according to some high-quality studies (Andersson et al, 2013;Merritt et al, 2017).…”
Section: Emotional Distressmentioning
confidence: 99%
“…The results uncovered three main themes: “Being less than a man”, “Facing a bleak future”, and “Life has lost its meaning”. 16 Other qualitative studies in Iran have assessed the experiences of male and female elderly with CAD from which the following themes emerged: “ Having lost peace”, “Finding peace in spirituality” and “Having lost ones health and sexuality”. 17 – 20 …”
Section: Introductionmentioning
confidence: 99%